2020
DOI: 10.1039/c9cp06279c
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen abstraction in astrochemistry: formation of ˙CH2CONH2 in the reaction of H atom with acetamide (CH3CONH2) and photolysis of ˙CH2CONH2 to form ketene (CH2CO) in solid para-hydrogen

Abstract: The amide bond of acetamide is unaffected by hydrogen exposure, but the hydrogen abstraction on its methyl site activates this molecule to react with other species to extend its size as a first step to form interstellar complex organic molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 64 publications
3
17
0
Order By: Relevance
“…The PES indicates that the reaction H + CH 3 C­(O)­OH → •CH 2 C­(O)­OH + H 2 has a relatively large barrier, 43 kJ mol –1 ; our experimental observation of •CH 2 C­(O)­OH at 3.3 K even in darkness indicates that this reaction occurred via tunneling. Similar H atom tunneling reactions have been observed for the reactions of H atoms with HONO (∼21 kJ mol –1 ), CH 3 OH (∼35 kJ mol –1 ), , H 2 NC­(O)H (∼26 kJ mol –1 ), C 5 H 5 N (∼8 kJ mol –1 ), HC­(O)­OCH 3 (∼41 and 46 kJ mol –1 for the formation of HC­(O)­CH 2 and C­(O)­OCH 3 radicals, respectively), and CH 3 CONH 2 (∼41 kJ mol –1 ); predicted barriers are provided in parentheses. Paulson et al photolyzed HC­(O)­OH in solid p -H 2 at 1.7 K with laser light at 193 nm and observed tunneling reaction H + HC­(O)­OH because some H atoms were produced from photolysis; the reaction proceeded even after photolysis was terminated, resulting in the formation of HOCO from abstraction of the hydrogen on the carbon atom rather than the hydroxyl hydrogen.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The PES indicates that the reaction H + CH 3 C­(O)­OH → •CH 2 C­(O)­OH + H 2 has a relatively large barrier, 43 kJ mol –1 ; our experimental observation of •CH 2 C­(O)­OH at 3.3 K even in darkness indicates that this reaction occurred via tunneling. Similar H atom tunneling reactions have been observed for the reactions of H atoms with HONO (∼21 kJ mol –1 ), CH 3 OH (∼35 kJ mol –1 ), , H 2 NC­(O)H (∼26 kJ mol –1 ), C 5 H 5 N (∼8 kJ mol –1 ), HC­(O)­OCH 3 (∼41 and 46 kJ mol –1 for the formation of HC­(O)­CH 2 and C­(O)­OCH 3 radicals, respectively), and CH 3 CONH 2 (∼41 kJ mol –1 ); predicted barriers are provided in parentheses. Paulson et al photolyzed HC­(O)­OH in solid p -H 2 at 1.7 K with laser light at 193 nm and observed tunneling reaction H + HC­(O)­OH because some H atoms were produced from photolysis; the reaction proceeded even after photolysis was terminated, resulting in the formation of HOCO from abstraction of the hydrogen on the carbon atom rather than the hydroxyl hydrogen.…”
Section: Discussionsupporting
confidence: 71%
“…These experiments are not meant to mimic the conditions in interstellar ices but rather serve as a model system to study the tunneling reactions of H atoms. In our previous investigations on reactions of H atoms with methanol CH 3 OH, formamide HC­(O)­NH 2 , methyl formate HC­(O)­OCH 3 , and acetamide CH 3 C­(O)­NH 2 , we found that the previously neglected H-abstraction plays an important role. For example, in the reaction H + HC­(O)­NH 2 , the dual-cyclic hydrogen-abstraction and hydrogen-addition connecting HC­(O)­NH 2 , H 2 NCO, and HNCO can explain the tight relation between astronomical abundances of HC­(O)­NH 2 and HNCO …”
Section: Introductionmentioning
confidence: 88%
“…CH 4 -HNCO ice mixtures at 20 K were irradiated with vacuum ultraviolet (VUV) photons to produce the radicals required for the formation of the amides, which then were identied by IR spectroscopy as well as mass spectrometry. 41 Recently, Haupa et al 45 found that the reaction of atomic hydrogen with acetamide in solid p-H 2 at 3.3 K produces the 2-amino-oxoethyl (cCH 2 CONH 2 ) radical, which further dissociates to ketene and cNH 2 upon UV/vis photolysis.…”
Section: Introductionmentioning
confidence: 99%
“…In the first set of experiments, H atoms were generated by the method described in the studies of Anderson as well as Lee and co-workers. For this, a second leak valve and stainless steel capillary were used to introduce Cl 2 to the main chamber. The SO 2 / para -H 2 ratio was 1:5500.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…It is taking advantage of the phenomenon of quantum diffusion that allows for the efficient movement of the H atoms through the matrix, facilitating H addition and abstraction reactions. Earlier studies in para -H 2 reported the successful hydrogenation of polycyclic aromatic hydrocarbons (PAHs), HONO, isoprene, propene, and pyrrole . Hydrogen abstraction from the isolated molecule by the H atoms could also be detected recently in the case of formamide, methyl formate, and acetamide. As it was shown by these studies, even if a H addition or a H abstraction reaction has a substantial barrier, it can be fast enough at very low temperatures due to H atom tunneling to observe it on the laboratory time scale. para -H 2 has a further important advantage; it is an excellent matrix material because it interacts weakly with the guest molecules.…”
Section: Introductionmentioning
confidence: 99%